The CORE (Consensus on Relevant Elements) Approach to Determining Initial Core Components of an Innovation - Kalver, Emily H.; McInnes, D. Keith; Yakovchenko, Vera; Hyde, Justeen; Petrakis, Beth Ann; Kim, Bo (Frontiers in Health Services, 2021)
Identifying an intervention’s core components is indispensable to gauging whether an intervention is implemented with fidelity and/or is modified; it is often a multi-stage process, starting with the first stage of identifying an initial set of core components that are gradually refined. This first stage of identifying initial core components has not been thoroughly examined. Without a clear set of steps to follow, interventions may vary in the rigor and thought applied to identifying their initial core components. We devised the CORE (Consensus on Relevant Elements) approach to synthesize opinions of intervention developers/implementers to identify an intervention’s initial core components, particularly applicable to innovative interventions. We applied CORE to a peer-based intervention that aids military veterans with post-incarceration community reintegration. Our CORE application involved four intervention developers/implementers and two moderators to facilitate the seven CORE steps. Our CORE application had two iterations, moving through Steps 1 (individual core component suggestions) through 7 (group discussion for consensus), then repeating Steps 4 (consolidation of component definitions) through 7. This resulted in 18 consensus-reached initial core components of the peer-based intervention, down from the 60 that the developers/implementers individually suggested at Step 1. Removed components were deemed to not threaten the intervention’s effectiveness even if absent. CORE contributes to filling a critical gap regarding identifying an intervention’s initial core components (so that the identified components can be subsequently refined), by providing concrete steps for synthesizing the knowledge of an intervention’s developers/implementers. Future research should examine CORE’s utility across various interventions and implementation settings.